Norway's sovereign wealth fund : ethical dilemmas - Osland, Asbjorn (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Norway's Government Pension Oil Fund Global (the Oil Fund) is funded by the excess revenues generated by Norway's oil and gas sales and income from existing holdings in the Oil Fund. It had grown to USD 1 trillion in assets, making it the world's largest sovereign wealth fund. The Council on Ethics (2016) advised the Oil Fund on what types of companies should be excluded for ethical violations. This came at the behest of several NGOs, with the concurrence of Parliament. Energy companies that derived 30% or more of their energy from coal should not be part of the Oil Fund; so too mining companies that derived over 30% of their revenues from coal were excluded. The irony was that the Oil Fund was financed by the sale of fossil fuels outside of Norway, which produced enormous amounts of greenhouse gas (GHG) emissions. As Signe Andresen and Marit Vik discuss the environmental, ethical, and decision-making issues around the Oil Fund's investments and management, key questions are raised. Should Norway's Oil Fund, which is dependent on excess revenues generated by Norway's oil and gas sales, take a strong stance against coal? Who would benefit from this stance? Should the Oil Fund promote non-renewable sources of energy use? If so, should it work with companies that are making progress away from coal or simply cut them off and remove their stocks from the portfolio?
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sovereign wealth funds -- Norway; Investments, Foreign -- Case studies; Petroleum industry and trade -- Norway